1995
DOI: 10.1111/j.1439-0523.1995.tb00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to fusarium wilt in chickpea

Abstract: This preliminary study indicated that the resistance to race 2 of fusarium wilt is controlled by two genes, the first of which must be present in the homozygous recessive form, and the other in the dominant form, whether homozygous or heterozygous for complete resistance. Early wilting results if the other gene is homozygous recessive. Late wilting occurs if both loci are dominant. The existence of differences among chickpea cultivars in the time taken to express the initial symptoms of fusarium wilt were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Interestingly, the third gene whether it is homozygous recessive or homozygous dominant or heterozygous, did not inXuence the expression of complete resistance by other two genes or imparted any role in complete resistance. The F 3 data of Kumar (1998) and that of F 2 of Gumber et al (1995) also did not Wt well to the three and two gene theories, respectively. This possibly points towards the involvement of fewer/more genes than three in race 2 resistance.…”
Section: Genetics Of Chickpea Wilt Resistancementioning
confidence: 46%
See 2 more Smart Citations
“…Interestingly, the third gene whether it is homozygous recessive or homozygous dominant or heterozygous, did not inXuence the expression of complete resistance by other two genes or imparted any role in complete resistance. The F 3 data of Kumar (1998) and that of F 2 of Gumber et al (1995) also did not Wt well to the three and two gene theories, respectively. This possibly points towards the involvement of fewer/more genes than three in race 2 resistance.…”
Section: Genetics Of Chickpea Wilt Resistancementioning
confidence: 46%
“…Phenomenon of late wilting was also reported after inoculation with race 2 (Gumber et al 1995). Of the three genes, a or b in homozygous recessive form or C in dominant form conferred late wilting (Kumar 1998).…”
Section: Genetics Of Chickpea Wilt Resistancementioning
confidence: 87%
See 1 more Smart Citation
“…Late wilting resistance is conferred by any one of these three genes, but a combination of any two of the late wilting genes confers complete resistance (h1h2 or h1H3 or h2H3) [12,23]. A similar genetic system based on two [70] or three [71] independent genes was found to confer resistance to race 2 [70,71]. Sharma et al [51] demonstrate that resistance to race 2 is governed by a single recessive gene, whereas resistance to race 3 has been found to be monogenic [51,72].…”
Section: Resistance To Fusarium Wiltmentioning
confidence: 99%
“…These late wilting lines may carry useful resistance genes that can confer complete resistance when complemented with other resistance genes. Gumber et al (1995) reported that resistance to race 2 of fusarium wilt is controlled by two genes, one gene must be present in the homozygous recessive form, and the second gene must have its dominant allele (whether in homozygous or heterozygous condition) for complete resistance. The resistance to race 4 of Fusarium oxysporum is controlled by a single recessive gene (Tullu et al, 1998).…”
Section: Fusarium Wiltmentioning
confidence: 99%